The Economic Price of Liquid Petroleum Gas, Poverty and Subsidy Removal Compensation Scenario in Indonesia - Prabowo, Eddy; Harianto; Juanda, Bambang; Indrawan, Dikky (International Journal of Energy Economics and Policy, 2022)
Indonesia is one of the countries with the largest population in the world, implicating the higher energy needs for consumption. LPG is one of the most important energies consumed by the majority of Indonesians since 2008. There is a programme for LPG in Indonesia, namely the LPG subsidy price. However, it is not implemented accurately in order to keep Indonesians, particularly those living below the poverty line able to purchase LPG. The purpose of this research is to determine the relationship between the economic price of LPG and poverty, as well as the subsidy removal compensation in Indonesia. Vector Auto Regression (VAR) first difference was applied in this research, and the findings show that statistically LPG economy prices have a unilateral relationship with a significant impact on poverty. Two subsidies removal compensation scenarios result shows that approximately subsidy of minimum IDR 52 thousand per month will keep the poor beneficiaries just above the poverty line. There is a potential government saving per year for LPG subsidies removal.